SYNTHESIS AND SIMULATION OF ELECTRIC DRIVES CONTROL SYSTEM OF ROLLING MILL CONVEYORS - D. N. Tsapko; S. V. Lukyanets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The structural diagram of electric drives conveyors power of rolling mill is offered, the synthesis of automatic control system controller and its simulation in a medium of Simulink is produced.